Human HMGB1 does not induce eryptosis in vitro - Maryna Tkachenko; Anatolii Onishchenko; Dmytro Butov; Tetyana Butova; Anton Tkachenko (National Scientific Medical Center, 2022)
Aim: To study the ability of human high mobility group box protein 1 (HMGB1) to induce eryptosis in vitro. Material and methods: Blood collected from six healthy volunteers was incubated with HMGB1 (0-0.2-1-5 ng per ml). Eryptosis of red blood cells was assessed by Annexin V staining and 2',7'-dichlorodihydrofluorescein diacetate (H2DCFDA) staining by flow cytometry. The forward scatter (FSC) fluorescence was used to evaluate the morphology of red blood cells. Results: Exposure of erythrocytes to HMGB1 did not affect the morphology of erythrocytes, evidenced by no changes in the percentage of cells with small volume, i.e. shrunken cells, and erythrocytes with large volume, i.e. enlarged cells. HMGB1 had no impact on phosphatidylserine externalization, which is confirmed by the absence of statistically significant changes in the amount of phosphatidylserine-displaying cells and the mean fluorescence intensity (MFI) values of Annexin V-FITC in cells exposed to different concentrations of HMGB1. Furthermore, H2DCFDA staining revealed that the HMGB1 did not induce oxidative stress. Conclusion: HMGB1 does not promote eryptosis of human erythrocytes at concentrations of up to 5 ng/ml. Key words: high mobility group box protein 1, erythrocytes, inflammation, cell death